Identification and characterization of gut-associated lactic acid bacteria isolated from the bean bug, Riptortus pedestris (Hemiptera: Alydidae) - Okhee Choi; Yeyeong Lee; Byeongsam Kang; Su Kyung Cho; Yongsung Kang; Dong-Wan Kang; Seul-Bi Lee; Sung-Mun Bae; Jinwoo Kim (PLoS ONE, 2023)
Lactic acid bacteria (LAB) are beneficial bacteria for humans and animals. However, the characteristics and functions of LAB in insects remain unclear. Here, we isolated LAB from the gut of Riptortus pedestris, a pest that is a significant problem in soybean cultivation in Korea, and identified two Lactococcus lactis and one Enterococcus faecalis using matrix-associated laser desorption/ionization-time of flight and 16S rRNA analyses. All three LAB strains survived at pH 8, and L. lactis B103 and E. faecalis B105 survived at pH 9 for 24 h. In addition, these strains survived well in simulated gastric juice of humans containing pepsin and exhibited high resistance to bile salts. Two strains of L. lactis and one of E. faecalis maintained constant density (> 104 colony-forming units [CFU]/mL) at pH 2.5, but viability at pH 2.2 was strain-dependent. The three LAB were reinoculated into second-instar nymphs of R. pedestris and colonized well, reaching a constant density (> 105 CFU/gut) in the adult insect gut. Interestingly, feeding of these LAB increased the survival rate of insects compared to the negative control, with the largest increase seen for L. lactis B103. However, the LAB did not increase the weight or length of adult insects. These results indicate that insect-derived LAB possess the traits required for survival under gastrointestinal conditions and have beneficial effects on insect hosts. The LAB infection frequency of the wild bean bug populations was 89% (n = 18) in Gyeongsangnam-do, South Korea. These LAB can be utilized as a novel probiotic in the cultivation of beneficial insects. This study provides fundamental information about the symbiosis between insects and LAB, and a novel concept for pest control.